Self-Efficacy, Work–Family Conflict, And Emotional Intelligence as Predictors of Employee Performance: Evidence From PT. Dwicitra Putra Mandiri - I Made Arya Setiawan; Putu Pradiva Putra Salain; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
The purpose of this study is to determine the extent to which self-efficacy, work-family conflict, and emotional intelligence influence employee performance at PT. Dwicitra Putra Mandiri. This study employs a quantitative approach using a survey method and multiple linear regression analysis, accompanied by the coefficient of determination, t-test, and F-test to examine the relationships between variables. Data was collected through a questionnaire distributed to all employees of PT. Dwicitra Putra Mandiri, with a total sample of 32 respondents selected via saturation sampling. The collected data was analyzed using multiple linear regression to determine the contribution of each independent variable, and the results were validated through t-tests and F-tests to ensure the accuracy of the analysis. The analysis results prove that each independent variable has a significant impact on employee performance. These findings indicate that the higher the self-efficacy, the more controlled the work-family conflict, and the better the emotional intelligence, the greater the improvement in employee performance achieved.